(untitled) (Anclajes, 2024)
The poetic group Cántico developed its work mainly between the 40s and 50s of the last century in Córdoba (Spain). Until 2011, the interest aroused in Hispanic literary historiography focused on the eccentric poetic space they occupied in post-civil war literature. The publication of the Diario by Juan Bernier, the main animator of the group, surprised and overwhelmed by the exhaustiveness and crudeness with which he reconstructs his homosexual pederastic practices, those of his companions and the repressive environment against dissent, specially through the mechanism of social shame. The comparison of two autobiographical texts, Bernier’s Diario and that of his groupmate, Ricardo Molina, allows us to discover the essential influence of André Gide’s pederastic ethical proposal. Studying this intellectual and literary ascendancy as a tolerated device for negotiating desire towards ephebes is an essential chapter of the contemporary homosexual archive.